2017
DOI: 10.1002/2016jc012171
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing frontal eddies along the East Australian Current from HF radar observations

Abstract: The East Australian Current (EAC) dominates the ocean circulation along south‐eastern Australia, however, little is known about the submesoscale frontal instabilities associated with this western boundary current. One year of surface current measurements from HF radars, in conjunction with mooring and satellite observations, highlight the occurrence and propagation of meanders and frontal eddies along the inshore edge of the EAC. Eddies were systematically identified using the geometry of the high spatial reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
87
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 50 publications
5
87
0
Order By: Relevance
“…Submesoscale motions have a variety of generation mechanisms including mixed layer instability, direct wind forcing, or Charney instability, all of which are sensitive to surface mixing and hence show a seasonal dependence (McWilliams, 2016). Here we resolve strong upstream WBC jets against the continental slope that undergo a weaker mixed layer depth seasonal cycle (Gula et al, 2014), with submesoscale frontal instabilities that are related to topographic interaction and exhibit no seasonal cycle (Lee & Mayer, 1977;Schaeffer et al, 2017). The studies above focused on open ocean areas where the mean current flow is weaker and mixed layer instabilities strengthen in winter with greater mixed layer depth.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Submesoscale motions have a variety of generation mechanisms including mixed layer instability, direct wind forcing, or Charney instability, all of which are sensitive to surface mixing and hence show a seasonal dependence (McWilliams, 2016). Here we resolve strong upstream WBC jets against the continental slope that undergo a weaker mixed layer depth seasonal cycle (Gula et al, 2014), with submesoscale frontal instabilities that are related to topographic interaction and exhibit no seasonal cycle (Lee & Mayer, 1977;Schaeffer et al, 2017). The studies above focused on open ocean areas where the mean current flow is weaker and mixed layer instabilities strengthen in winter with greater mixed layer depth.…”
Section: Discussionmentioning
confidence: 87%
“…Remote wind forcing, communicated via first mode baroclinic Rossby waves, has been shown to affect the annual cycle in volume transport (Domingues et al, 2016), but for the data presented here at 25-26°N, the Bahamas island chain blocks most of this direct mid-ocean influence (Archer, Shay, et al, 2017). At 30-31°S, the EAC has a mean core speed between 0.6 and 1.35 m s À1 (Archer, Roughan, et al, 2017;Mata et al, 2000;Schaeffer et al, 2017) and a volume transport of~22 Sv with an STD of~5-7 Sv (Mata et al, 2000;Sloyan et al, 2016). The EAC closes the South Pacific subtropical gyre, flowing poleward along SE Australia (Figure 1b).…”
Section: Introductionmentioning
confidence: 76%
“…The existence and importance of topographically-induced secondary circulations, small scale eddies and upwelling around reef islands in the GBR has been extensively documented (e.g. White and Wolanski [42]) while submesoscale features (3-10 km) are relevant in the Coffs Harbour region (Mantovanelli et al [43], Schaeffer et al [44]). …”
Section: Discussionmentioning
confidence: 99%
“…Errors in the HF radar currents become significant in water shallower than about 5 m for a ~8 MHz radar transmit frequency (Lipa et al [44]), as used in the GBR radar system and hence may become significant near the reefs if the radar cell includes shallow/exposed areas.…”
Section: Discussionmentioning
confidence: 99%
“…Bowen et al () showed that the eddy field of the EAC system undergoes spatiotemporal variability, as the peak variance of their altimetry‐derived stream function moved from 30°S–32°S to 33°S–35°S, between 1993 and 1998. In the submesoscale range, cyclonic frontal eddies have been observed in high frequency (HF) ocean radar maps, propagating poleward inshore of the EAC, irregularly timed but on average one per week, with inshore radii of ∼10 km (Schaeffer et al, ). These small‐scale eddies are associated with Rossby numbers of order 1 and intense, asymmetrical vorticity and divergence fields (Mantovanelli et al, ), and high productivity (Roughan et al, ).…”
Section: Introductionmentioning
confidence: 99%